Alarming Cases of Cancer in Kenya: A case for Meru and Tharaka Nithi Counties - Mutiso, Joshua; Gitonga, Ciriaka; Abdullahi, Bulle; Simbauni, Jemimah; Gicheru, Michael (British Journal of Healthcare and Medical Research, 2023)
Background: Cancer is one of the leading causes of morbidity and mortality worldwide. In Kenya, cancer as a disease ranks third as a cause of death after infectious and cardiovascular diseases and the cancer cases are increasing at an alarming rate. Objective: The current study was aimed at determining the prevalence trends of cancer in Meru and Tharaka Nithi Counties with an aim of putting proper infrastructural and human capacity development to combat cancer. Methods: A random selection of patients aged between five to eighty-two years clinically diagnosed as cancer patients who were visiting Meru and Chuka General Hospitals for a period of one year were recruited for the study. The participants were requested to give a verbal consent and respond to a brief questionnaire concerning their gender, age and the type of cancer they are suffering from. This study used retrogressive approach where the trend of cancer incidences and death rate were determined for the last eight years (2011 to 2018) using the hospital data. Data were analysed using statistical package for social sciences (SPSS). Results: This study established that the prevalence of cancer in people visiting hospitals in Meru and Tharaka Nithi Counties was 0.32% and 0.38% respectively. Further, the prevalence trends of cancer cases in the two counties have been increasing over the last eight years. Conclusion: The study concludes that cancer is prevalent in Meru and Tharaka Nithi Counties. It is therefore recommended that proper infrastructural and human capacity development be put in place to combat cancer.